HOME INDUSTRY PAKAIAN DI PEDESAAN SUMATERA: MELIHAT SISI KESEJAHTERAAN SUBJEKTIF DAN DAMPAK KESEJAHTERAAN - Risma Nia; Muhammad Izzudin (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Subjective well-being is a cognitive assessment of life satisfaction, which means a comprehensive assessment of an individual's assessment of various areas of life in which he has lived well or not and an affective assessment of feelings and emotions that concurrently produce positive emotions (pleasant) and negative emotions (unpleasant). This study used descriptive qualitative research methods with a purposive selection of informants. The results showed that the subjective welfare felt by clothing home industry workers in Seri Tanjung Village was analyzed from the cognitive dimension and affective dimension, namely clothing home industry workers can meet their daily needs, comfortable with their work, want to improve the quality of family life, can relate well with fellow colleagues, have support from family, are optimistic about completing work or stitch targets, and there are obstacles (negative emotions) in facing work such as customers want to change clothing models, orders are canceled, stitches and sequins are wrong, sewing machines are damaged, power goes out, targets are not met due to worker permits, and difficulty cutting batik patterns. Then the impact of the clothing home industry business for the clothing home industry workers is to have income (increase family income) and skills (open job opportunities). Keywords: Subjective Well-Being; Industry Home Workers; Clothing AbstrakKesejahteraan subjektif (subjective well-being) adalah penilaian kognitif terhadap kepuasan hidup yang bermakna penilaian seorang individu secara menyeluruh terhadap berbagai bidang dalam kehidupan yang dijalaninya sudah berjalan baik atau tidak dan penilaian afektif terhadap perasaan dan emosi yang merangkap emosi positif (menyenangkan) dan emosi negatif (tidak menyenangkan). Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan pemilihan informan secara purposive. Hasil penelitian menunjukkan bahwa kesejahteraan subjektif yang dirasakan pekerja home industry pakaian di Desa Seri Tanjung dianalisis dari dimensi kognitif dan dimensi afektif yaitu para pekerja home industry pakaian bisa mencukupi kebutuhan sehari-hari, nyaman atas pekerjaannya, ingin memperbaiki kualitas hidup keluarga, bisa berhubungan baik dengan sesama rekan kerja, ada dukungan dari keluarga, optimis menyelesaikan pekerjaan atau target jahitan, dan ada kendala (emosi negatif) dalam menghadapi pekerjaan seperti pelanggan ingin ganti model baju, orderan dibatalkan, hasil jahitan dan payetan salah, mesin jahit rusak, listrik padam, target tidak terpenuhi karena pekerja izin, dan kesulitan memotong batik pola. Kemudian dampak usaha home industry pakaian di Desa Seri Tanjung bagi pekerja home industry pakaian tersebut yaitu punya penghasilan (meningkatkan pendapatan keluarga) dan punya skill (membuka lapangan pekerjaan). Kata Kunci: Kesejahteraan Subjektif; Pekerja Home Industry; Pakaian